Unusual case of intraperitoneal round ligament fibroid, mimicking ovarian carcinoma - Kaur, Ramneet; Patankar, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Round ligament leiomyoma are extremely rare benign tumors. It may present with wide range of clinical presentations depending on its site of origin, on the long course of round ligament. It has been reported round ligament leiomyoma commonly arises from extra peritoneal end of round ligament. There have been case reports where round ligament fibroid have presented like incarcerated inguinal hernia, vulvar swelling, inguinal lymph node. We present a case of intraperitoneal round ligament leiomyoma. A 40 year old female presented to gynecology Opd with a pain abdomen, abdominal distension and a mass of 26-28 weeks size gravid uterus, pelvic in origin. Her CA-125 level was 185 U/ml, CT abdomen suggested neoplastic ovarian tumor. With provisional diagnosis of ovarian carcinoma, patient was taken for exploratory laparotomy. Intraoperative findings suggested mass arising from intraperitoneal part of round ligament, with solid and cystic component and ascites. Bilateral ovaries and tubes were healthy and separately seen from mass. Histopathology report confirmed leiomyoma with hyaline and cystic degeneration. Large round ligament leiomyoma with degenerative changes can mimic ovarian carcinoma on imaging. A tissue biopsy or MRI before surgery can be of help.